(untitled) (International Journal of Nursing Education, 2023)
Teamwork and collaboration are inherent to the work of a nurse. In a post-pandemic nursing education world, students need more opportunities to collaborate and work as a team. Clinical and classroom strategies in nursing education are often group-based to help support development of teamwork and collaboration skills. Testing is often omitted from being group-based but could be included as a strategy to increase teamwork and collaborative skills. The purpose of this study was to examine the effect of collaborative testing on teamwork and collaboration in nursing students. Post-implementation survey results provided support for the continued used of collaborative testing as the overall outcomes were positive.